Weathervanes [compact disc] - Isbell, Jason (Southeastern Records, 2023)
Jason Isbell and the 400 Unit tackle issues such as gun violence, the opioid crisis, and women's rights, all through Isbell's signature songwriting lens. It is a collection of grown-up songs: songs about adult love, about change, about the danger of nostalgia and the interrogation of myths, about cruelty, regret, and redemption. Life and death songs played for and by grown-ass people. Some will make you cry alone in your car and others will make you sing along with thousands of strangers in a big summer pavilion.